Supervisi dan Sosialisasi sebagai Upaya Optimalisasi Pelaksanaan Serah Terima Pasien Antar Shift dengan Metode SBAR - Erwin; Damayanti, Mira; Afriani, Tuti; Suminarti, Tini (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Background: Patient handover is the process of communicating patient information for the continuity of thepatient care process. The SBAR method can be used as a guide in prompt and precise patient handover in thefield of health services. Purpose: This study discusses the problem of implementing inter-shifting patienthandover at Hospital X and developing problem solving solutions. Method: A pilot study using Kurt Lewin'splanned change theory. Data collection is done by interviews, questionnaires and observations. Results: thepercentage of achievement of the handover of 78.47% and the analysis of the fishbone diagram of inter-shiftpatient handover assessment by the SBAR method at X Hospital was not optimal. The socialization of handoverand supervision instruments was developed as a solution to solving the problem. Conclusion: Follow-upimprovements and product endorsements need to be done as an effort to optimize the delivery of patients. Thenursing manager is expected to perform the supervisory management function to improve the sustainability andsustainability of these efforts.